Effect of planetary ball milling on physicochemical and morphological properties of sorghum flour - Palavecino, Pablo Martín (2019)
Planetary ball milling was applied to white sorghum flour with the aim of modifying its thermal, structural and morphological properties. Median particle size decreased from 57.2 μm a 20.8 μm with increasing milling energy. Particle size-energy models indicated that only part of the energy was used for developing new surfaces. Abrasion of starch granules could be observed by SEM and the increment of damaged starch levels. Gelatinization temperatures measured by DSC were not affected by the process (Tp average 73.4 ± 0.4 °C); yet, gelatinization enthalpy (ΔH) and crystallinity degree (determined by WAXS) decreased with increasing milling energy from 5.54 J/g and 28% to 2.98 J/g and 17.0%, respectively. Then, some pasting parameters significantly changed: final viscosity (from 3947 to 3535 cP) and, consequently, setback (from 2339 to 1896 cP). Planetary ball milling significantly changed the functional properties of sorghum flour and suggested that this method is an alternative to widen sorghum flour food applications.